Globalisation and Critical Cosmopolitanism in Contemporary British Fiction - Zhao, Yang (2022)
This thesis investigates the connection between globalisation and the prospect of cosmopolitanism by examining four contemporary British works of fiction. The concept of cosmopolitanism concerns people’s open attitudes towards foreign others and their endeavour to reach out across differences. New cosmopolitanism arises in the context of globalisation: it is embedded in locality and stems from the situation of global coexistence and multicultural conviviality. In this thesis, the fictions I examine are Kazuo Ishiguro’s The Unconsoled (1995), Zadie Smith’s On Beauty (2005), Nadeem Aslam’s Maps for Lost Lovers (2004), and Hari Kunzru’s Transmission (2004). The issues I address in my analyses include the radical East/West encounter after 1989, the new condition of ‘glocalisation’, the dynamics within diasporic communities and the rise of cosmopolitan culture, and the emergence of new media and technology in the age of informatisation. The thesis is structured both thematically and chronologically: while each chapter addresses a different aspect of cosmopolitanism, the topics under discussion are sequenced according to their relevance to contemporary life. The thesis as a whole illuminates the complexity of contemporary cosmopolitanism: the fictions collectively demonstrate both the challenges and possibilities in envisioning cosmopolitanism in the context of globalisation.